Host Plant Catalog of Aphids Palaearctic Region - Holman, Jaroslav (Springer Netherlands : Imprint: Springer, 2009)
Host Plant Catalog of Aphids in the Palaearctic Region; J. Holman The major part of this Catalog presents host lists of particular aphid species in the Palaearctic Region based on published data and more than 2,400 author's unpublished host records, with respective references arranged by geographical provenance. The book includes separate lists of aphids living on particular plants, arranged in alphabetical order of plant families and genera, separately for mosses, ferns, gymnosperms, dicotyledons and monocotyledons. The coverage is exhaustive, including some 3,706 aphid species (about 80 per cent of the aphid fauna of the world), feeding on 11,131 species of host plants in 1,948 genera and 243 families. Host Plant Catalog of Aphids combines well-organized data with up-to-date information on geographic distribution of particular aphid species and their host relationships. It will be a useful addition to the libraries of institutions and researchers interested in biosystematics, ecology, genetics and phylogeny of aphids, as well as in biodiversity and plant protection.